Gastrodia damingshanensis (Orchidaceae: Epidendroideae): a new myco-heterotrophic orchid from China - Hu, Ai-Qun; Hsu, Tian-Chuan; Liu, Yan (Phytotaxa, 2014)
A new fully myco-heterotrophic orchid, Gastrodia damingshanensis, is described and illustrated from Damingshan National Nature Reserve in Guangxi, China. The new species is significantly distinct from the otherwise similar G. uraiensis and G. fontinalis by its much longer peduncle, the shortened column hidden by the lip, and the reddish brown, rhombic-elliptic lip with a slightly retuse apex. This new species is predicted to be obligatory self-pollinated due to the specialized column structure which allows the pollinia directly touching the stigma.